FEZF1-AS1 drives autophagy-mediated progression of colon cancer and reduces chemosensitivity through inhabiting the PI3K/AKT/mTOR signaling pathway - Yang, Xiaoping; Yuan, Zuohui; Gou, Lingzhu; Cheng, Long; Wang, Zirui; Wu, Pingfan; Wang, Xiaochun; Ma, Xueni; Ma, Tiantian; Yu, Yi; Wu, Zhiping; Zhang, Dekui (Frontiers in Genetics, 2025)
The pathogenesis and chemoresistance mechanisms of colon cancer (CC) are still unclear. Here, we find that a long non-coding RNA (lncRNA), FEZ family zinc finger 1-antisense RNA 1 (FEZF1-AS1), is highly expressed in CC, which may be caused by the amplification mutation of FEZF1-AS1 at the gene level through bioinformatic analysis. FEZF1-AS1 has the potential to be a biomarker in the diagnosis of CC. Functionally, FEZF1-AS1 promotes the proliferation, invasion, metastasis, and survival of CC cells and reduces the sensitivity of CC cells to oxaliplatin. Mechanistically, FEZF1-AS1 drives autophagy-mediated development of CC and reduces chemosensitivity to oxaliplatin through inhabiting the PI3K/AKT/mTOR signaling pathway. In summary, our data suggest that FEZF1-AS1 may be a key driver of CC progression and chemotherapy resistance, and targeting FEZF1-AS1 may be a potential strategy for the diagnosis and treatment of CC.